2015
DOI: 10.1371/journal.pone.0124811
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification and Characterisation of Silk Fibroin Fabric Produced by the Layer-by-Layer Self-Assembly of Multilayer Alginate/Regenerated Silk Fibroin

Abstract: Silk-based medical products have a long history of use as a material for surgical sutures because of their desirable mechanical properties. However, silk fibroin fabric has been reported to be haemolytic when in direct contact with blood. The layer-by-layer self-assembly technique provides a method for surface modification to improve the biocompatibility of silk fibroin fabrics. Regenerated silk fibroin and alginate, which have excellent biocompatibility and low immunogenicity, are outstanding candidates for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 56 publications
4
23
0
Order By: Relevance
“…It is observed that in both the studies, [6][7][8]17 with only subtle increments of CNTs, mechanical properties of CHI polymer matrices can be substantially improved, and that both HA and CNTs are evenly distributed in CHI matrix.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It is observed that in both the studies, [6][7][8]17 with only subtle increments of CNTs, mechanical properties of CHI polymer matrices can be substantially improved, and that both HA and CNTs are evenly distributed in CHI matrix.…”
Section: Discussionmentioning
confidence: 88%
“…The composites based on Hydroxyapatite, Carbon Nanotubes with Biopolymers are excellent candidates for application in bone grafts and coating of bone prostheses, due to their mechanical properties, to promote osteogenesis and reduce bacterial fixation. [6][7][8][9] The purpose of the manuscript is to analyze and compare data from the current state of the art of CHI matrix composites with HA and CNTs applied in bone tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…As all biomaterials approved by the FDA exhibit no cytotoxicity, some of the more likely sources of problems associated with biomaterials may involve their structural parameters as well as the chemical structure of the material . As an approach to rectify these problems many attempts have been employed to change the structure of surface chemicals to promote cell adhesion and proliferation as achieved with the use of layer by layer or surface grafting . However, for a woven fabric, such as polyethylene glycol terephthalate (PET), the structural parameters seem to exert a greater impact upon cell adhesion than that of the chemical structure .…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, a considerable amount of effort has been directed at improving the biocompatibility of biomaterials in order to reduce such complications. Some examples of these attempts have included a layer by layer assembly, surface grafting and alterations in surface morphology . Ranella et al, utilized the microstructure of nanosilicon materials as an approach to impact cell adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Some examples of these attempts have included a layer by layer assembly, surface grafting and alterations in surface morphology. [3][4][5][6][7][8][9] Ranella et al, 5 utilized the microstructure of nanosilicon materials as an approach to impact cell adhesion. With the use of a femtosecond laser, they produced silicon wafers with different surfaces that varied from smooth to very coarse.…”
Section: Introductionmentioning
confidence: 99%